Respuesta :
Answer:
f(n)=6n+5
Step-by-step explanation:
since the second term is 13, we have to subtract 6 to get our first term, 5.
Then we put it together,
I hope this helps you
If it does a thanks (and brainliest trying to level up) would be appreciated, if wrong please leave a comment
Answer:
[tex]a_{n}[/tex] = 6n + 1
Step-by-step explanation:
This is an arithmetic sequence with n th term
[tex]a_{n}[/tex] = a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = a₂ - 6 = 13 - 6 = 7 and d = 6, thus
[tex]a_{n}[/tex] = 7 + 6(n - 1) = 7 + 6n - 6 = 6n + 1